LINGUOCULTURAL COMPARATIVE ANALYSIS OF IDIOMS IN ENGLISH AND UZBEK LANGUAGES - Ashurova, Maftuna; Yuldoshev, Rustam (Ижтимоий-гуманитар фанларнинг долзарб муаммолари / Актуальные проблемы социально-гуманитарных наук / Actual Problems of Humanities and Social Sciences., 2023)
The article deals with the lingual analysis of idioms comparison in Uzbek and English languages. The aim of the article is basically to illustrate language, culture, idioms, and their relationship with the foreign language. It investigates the significant features of idioms and their relationship with language and culture is illustrated in this article and give some idiomatic expressions with its definition.